11 First, Do No Harm. Improving Safety in Catheter Ablation for Atrial Fibrillation: A Prospective Study of the Use of Ultrasound to Guide Vascular Access. (31st May 2014) - Wynn, Gareth; Haq, Iram; Hung, John; Bonnett, Laura; Webber, Matthew; Das, Moloy; Kennedy, Tom; Waktare, Johan; Modi, Simon; Snowdon, Richard; Hall, Mark; Lewis, Gavin; et al.
Abstract : Introduction: The most frequent complications of AF Ablation (AFA) are related to vascular access but there is little published evidence as to how these can be minimised. In 2012 the European Society of Cardiology clearly stated in their updated guidelines that "improving safety of catheter ablation should be a primary goal in the further development of this therapy". Methods: In this prospective study, consecutive patients undergoing AFA received either standard femoral vascular access, guided by a landmark technique (Group S), or routine ultrasound-guided vascular access (Group U). Vascular complications were assessed before hospital discharge, and by means of bespoke postal questionnaire one month later. Outcome measures were actionable (BARC2+) bleeding complications, groin pain that required analgesics, and prolonged bruising lasting >2 weeks. Results: Patients in Groups S (n = 146) and U (n = 163) were well matched at baseline. Follow up questionnaires were received from 92.6% of patients. Uninterrupted warfarin therapy was used in 65% of cases. There was no difference between the groups in mean INR levels, peak ACT levels or in the use of protamine post-procedure. Procedures in Group U were significantly shorter than those in Group S (184 ± 53 min v. 167 ± 4 min, p = 0.04). Inadvertent femoral arterial puncture, as recognised by the operator, was less common in Group U (10, 6.1%) than in Group S (19, 13.0%), p = 0.04. Patients in Group U were significantly less likely to have a BARC 2+ bleed (10.4% v. 19.9% p = 0.02), were less likely to suffer groin pain after discharge (27.1% v. 42.8%, p = 0.006) and were less likely to experience prolonged local bruising (21.5% v. 40.4% p = 0.001). 2 patients in Group S and 1 patient in Group U had major (BARC 3) bleeding requiring blood transfusion (p = NS). Multivariable logistic regression analysis revealed a significant association of vascular complications with non-ultrasound guided access (OR 3.12 95% CI 1.54–5.34, p = 0.003) and increasing age (OR 1.05 95% CI 1.01–1.09 p = 0.02). The number needed to treat with ultrasound to prevent one bleeding complication was 11. Discussion: Previous work has shown that physician-reported complication rates following AFA miss the majority of vascular events considered important to patients. For this reason we assessed patient reported outcome measures post-discharge, and chose a broad definition of bleeding complications rather than restricting ourselves to life-threatening complications. Accordingly our complication rates seem high at first glance, but we believe they better represent the true patient experience. To our knowledge, this is the first study to show the benefit of adopting a policy of using vascular ultrasound for AFA. Conclusion: Routine use of ultrasound guided vascular access for AFA is associated with a significant reduction in bleeding complications, post procedural groin pain and prolonged local bruising when compared to standard vascular access.